Integration of Wind Catchers in Modern Residential Buildings in the UAE as a Means of Providing Thermal Comfort - Riza, Raashid (2014)
This research is an evaluation of the effectiveness of wind catchers as means of providing thermal comfort for modern residential buildings in the hot arid climates in the UAE. Though this research involves a residence in Abu Dhabi as a case study, it stresses that the results obtained can be used for other regions with similar climates and in most instances are largely applicable. A computer simulation tool, IES VE 2013, is used as a methodology to model spaces and different configurations that consist of the following parameters, are tested: floor to ceiling height of the space, area of the window opening, height of the wind tower, orientation of the wind tower, percentage opening of the window and the percentage opening of the wind tower opening. An automatic condition profile is imposed on the window and wind tower openings by the software so that they open and function only when these conditions are satisfied. The study initially reviewed literature already existing on the integration of traditional sustainable techniques in the UAE. Further studies were done on how integral wind catchers were in traditional architecture to provide cooling for occupants in residences. The simulations were carried out in two steps. As a first step, the case study building as it exists was subjected to a thermal simulation analysis. Results were obtained in terms of annual hours within the human thermal comfort range and Degree Discomfort Hours (DDH). The second step involved carrying out a series of simulations according to a test matrix, results obtained were analysed in comparison to the existing case. Of the configurations tested, the optimal configuration bore the following characteristics: Floor to Ceiling Height of 6m, wind tower height of 9m with North West orientation, window area of 3 m2, wind tower opening of 2 m2, Percentage window opening of 100% and a percentage of wind tower opening 100%. The optimal configuration when tested resulted in 47.1% decrease in degree discomfort hours and a 22.1% increase of hours annually in the thermal comfort range when compared to the existing case. Furthermore, when the existing case was re-simulated with a cooling device switched on, it was estimated that the existing case consumes 39.5% more energy than the optimal configuration. The study concludes by identifying guidelines for the implementation and use of wind towers in the modern age and with recommendations for future research.